2016
DOI: 10.1016/j.nano.2015.10.010
|View full text |Cite|
|
Sign up to set email alerts
|

Gold nanoparticle conjugated Rad6 inhibitor induces cell death in triple negative breast cancer cells by inducing mitochondrial dysfunction and PARP-1 hyperactivation: Synthesis and characterization

Abstract: We recently developed a small molecule inhibitor SMI#9 for Rad6, a protein overexpressed in aggressive breast cancers and involved in DNA damage tolerance. SMI#9 induces cytotoxicity in cancerous cells but spares normal breast cells; however, its therapeutic efficacy is limited by poor solubility. Here we chemically modified SMI#9 to enable its conjugation and hydrolysis from gold nanoparticle (GNP). SMI#9-GNP and parent SMI#9 activities were compared in mesenchymal and basal triple negative breast cancer (TNB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 53 publications
2
35
0
Order By: Relevance
“…We would expect to emulate the results obtained with inhibitors of other E2 enzymes, such as in the case of small molecule inhibitor SMI # 9 for Rad6 in triple negative breast cancer. This molecule, beyond the problems faced in conveying the drug, has been shown to induce cytotoxicity in breast cancer cells but spares normal breast cells and demonstrated efficacy in combination with cisplatin [65]. In our opinion, the data accumulated in recent years concerning UbcH10 are solid and promising, and should not be forgotten.…”
Section: Discussionmentioning
confidence: 95%
“…We would expect to emulate the results obtained with inhibitors of other E2 enzymes, such as in the case of small molecule inhibitor SMI # 9 for Rad6 in triple negative breast cancer. This molecule, beyond the problems faced in conveying the drug, has been shown to induce cytotoxicity in breast cancer cells but spares normal breast cells and demonstrated efficacy in combination with cisplatin [65]. In our opinion, the data accumulated in recent years concerning UbcH10 are solid and promising, and should not be forgotten.…”
Section: Discussionmentioning
confidence: 95%
“…Ubiquitin Conjugating Enzyme E2 A (UBE2A), also known as RAD6A, is a ubiquitin conjugating enzyme which is involved in protein metabolism. Studies showed that UBE2A is upregulated in aggressive breast cancers and its expression correlates with metastasis [88] [89]. In one study, authors also revealed that increased RAD6 levels are associated with cancer stem cell phenotype in ovarian cancer resulting in disease recurrence and metastasis [90].…”
Section: Bad Prognostic Genesmentioning
confidence: 99%
“…NPMBC possess cytotoxic activity per se [39,66,67,69]; however, their main applications are related to their ability to act as radiosensitizers in cancer cells through the induction of G2/M phase cell cycle arrest [36,47,66], as agents for PCT applications [14,28,29,37,63] or as transmembrane carriers for the controlled release and targeted delivery of anticancer drugs increasing their cellular uptake [30,39,40], among others [47,64]. Cancer cells in a tumor are very heterogeneous, that is, they differ in marker expression, morphology, proliferation capacity, growth stage, etc.…”
Section: Suppression Of Cancer Cell Viability In Association With Thementioning
confidence: 99%
“…However, both cisplatin chemotherapies and its analogs have been shown to have major drawbacks (i.e., intrinsic and acquired chemoresistance, high general toxicity and limited spectrum of activity) [26] which have motivated extensive investigations into alternative metal-based cancer therapies that effectively target both cancer cell proliferation and metastasis. In this sense, we can mention chemotherapy with gold compounds [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46]-because they are nontoxic, nonimmunogenic and have good photothermal and optical properties, biocompatibility and stability [40,47,48]-and also with copper [49][50][51], ruthenium [16,[52][53][54][55][56][57][58][59], iron [56,[60][61][62][63][64][65], palladium [50], silver [66,…”
Section: Introductionmentioning
confidence: 99%